Medical implementation practice and its medical performance evaluation of a giant makeshift hospital during the COVID-19 pandemic: An innovative model response to a public health emergency in Shanghai, China - Chen, Minjie; Fan, Yiling; Xu, Qingrong; Huang, Hua; Zheng, Xinyi; Xiao, Dongdong; Fang, Weilin; Qin, Jun; Zheng, Junhua; Dong, Enhong (Frontiers in Public Health, 2023)
In confronting the sudden COVID-19 epidemic, China and other countries have been under great pressure to block virus transmission and reduce fatalities. Converting large-scale public venues into makeshift hospitals is a popular response. This addresses the outbreak and can maintain smooth operation of a country or region’s healthcare system during a pandemic. However, large makeshift hospitals, such as the Shanghai New International Expo Centre (SNIEC) makeshift hospital, which is the largest makeshift hospital in the world, face two major problems: effective and precise transfer of patients and heterogeneity of the medical care teams. To solve these problems, this study presents the medical practices of the SNIEC makeshift hospital in Shanghai, China. The experiences include constructing two groups, developing a medical management protocol, implementing a multi-dimensional management mode to screen patients, transferring them effectively, and achieving homogeneous quality of medical care. To evaluate the medical practice performance of the SNIEC makeshift hospital, 41,941 infected patients were retrospectively reviewed from March 31 to May 23, 2022. Through multivariate logistic regression and a tree-augmented naive (TAN) Bayesian network model, we identified that the three most important variables were chronic disease, age, and type of cabin, with importance values of 0.63, 0.15, and 0.11, respectively. The constructed TAN Bayesian network model had good predictive values; the overall correct rates of the model-training dataset partition and test dataset partition were 99.19% and 99.05%, respectively, and the respective values for the area under the receiver operating characteristic curve were 0.939 and 0.957. In conclusion, the medical practice in the SNIEC makeshift hospital was implemented well, had good medical care performance, and could be copied worldwide as a practical intervention to fight the epidemic in China and other developing countries.